2019
DOI: 10.1111/scd.12444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral conditions of children/adolescents with Down syndrome on their families’ quality of life

Abstract: Aims To assess the impact of oral conditions among children/adolescents with Down syndrome (DS) on the Oral Health‐related Quality of Life (OHRQoL) of their families in comparison with a group without DS. Methods and results Families of 144 children/adolescents with DS aged 4‐18 years were compared with families of individuals without DS. Dental caries experience (DMFT/dmft), clinical consequences of untreated dental caries (PUFA/pufa), gingival bleeding (GBI), visible plaque (VPI), and malocclusion were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
0
24
0
6
Order By: Relevance
“…In their recent study, Carrada et al assessed caregivers' perceptions of the quality of life of children with Down syndrome [10]. Their findings revealed that presence of dental caries, severe malocclusion, and defined malocclusion had negative impacts on both children's and their families' OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their recent study, Carrada et al assessed caregivers' perceptions of the quality of life of children with Down syndrome [10]. Their findings revealed that presence of dental caries, severe malocclusion, and defined malocclusion had negative impacts on both children's and their families' OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Although no association between poor oral health and mortality has been established, it adversely affects morbidity and might exacerbate the existing diseases and conditions [7], thus increasing the burden on individuals and governments [7]. Although the link between poor oral health and individuals' wellbeing and quality of life (QoL) [8,9] is well established, limited research focusing specifically on individuals with Down syndrome exists [10][11][12][13]. The available evidence, however scant, points to negative impacts of oral health status on the quality of life in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Kondisi kesehatan fisikindividu SD merupakan faktor yang dapat berpengaruh pula pada kualitas hidup caregivers. Hasil yang samadaripenelitian yang dilakukan oleh (Choi, E.K., 2019& Carrada, 2019 bahwa kondisi medis seperti disfungsi usus dan kandung kemih, masalah kesehatan gigi dan masalah tidur pada anak SD adalahmasalah yang paling seringditemukan pada individu DS, yang secaralangsungmemberikanbebankepada orang tuaatau caregiver individu DS. Menurut penulis, anak dengan DS dengan beragam kekurangannya, baik kondisi medis, fisik maupun mental menjadi beban tersendiri bagi caregiverskarenatidakhanyakondisiketerbelakangan mental sampaiseumurhiduptetapi juga banyaknyapenyakitpenyerta.…”
Section: Diskusiunclassified
“…Kondisi kesehatan fisik individu SD merupakan faktor yang dapat berpengaruh pula pada kualitas hidup caregivers. Hasil yang sama dari penelitian yang dilakukan oleh (Choi, E.K., 2019& Carrada, 2019 bahwa kondisi medis seperti disfungsi usus dan kandung kemih, masalah kesehatan gigi dan masalah tidur pada anak SD adalah masalah yang paling sering ditemukan pada individu DS, yang secara langsung memberikan beban kepada orang tua atau caregiver individu DS. Menurut penulis, anak dengan DS dengan beragam kekurangannya, baik kondisi medis, fisik maupun mental menjadi beban tersendiri bagi caregivers karena tidak hanya kondisi keterbelakangan mental sampai seumur hidup tetapi juga banyaknya penyakit penyerta.…”
Section: Diskusiunclassified